Effects of acid mine drainage on the genetic diversity and structure of a natural population of Daphnia longispina - Martins, Nelson (2009)
http://www.sciencedirect.com/science/article/B6T4G-4VGF3P1-4/2/c9f2ef3901010c151f4c562f8977cac0